La institucionalización de la mediación: potencialidades y riesgos - Caser, U.; Ramos, R. (Oñati Socio-legal Series, 2019)
On 27 and 28 April 2017, the International Institute for the Sociology of Law held a workshop under the theme The Institutionalization of Mediation: Potentialities and Risks. The scientific coordinators of this initiative promoted a structured discussion to identify the risks and potentialities of institutionalization to further develop mediation in the region. This article intends to review some literature supporting the subject of discussions, and to report the intense final discussion within the group of 27 mediation experts (from Germany, Belgium, France, Spain and Portugal). In these final reflections, we do not want to provide definitive answers to burning questions, but we hope to shed a light on the crucial dilemmas as they were discussed in a world-café-like workshop at the end of the meeting. Some limitations and future directions are discussed in light of participatory methods and governance innovation.